Credit unions, co-operatives, sustainability and accountability in a time of change: A case study of credit unions in Cyprus - Kleanthous, Akis; Paton, Robert A.; Wilson, Fiona M. (My University, 2019)
Purpose: The financial crisis of 2008 resulted in calls for change. Commentators suggested that co-operatives, in particular credit unions, could provide accountability and sustainability through their open governance and mutual status. However, such suggestions assumed that co-operative principles and practice continued to underpin the efficacy of co-operative banking, and that credit unions, one of the most prevalent forms of co-operative banking, could offer a viable financial alternative. Instead, in the case of Cyprus, the financial crisis and the associated aftershocks triggered the nationalisation and demutualisation of credit unions. This prompted the researchers to question both the viability of a co-operative banking future and the extent to which co-operative principles were shaping decision making, governance, accountability and sustainability. The paper aims to discuss these issues. Design/methodology/approach: A case study approach was adopted to explore the degree to which co-operative principles still shaped credit union thinking and stakeholder relationships. Findings: As is the case elsewhere within the co-operative movement, the findings point the fact that governance is weaken by the low membership participation and that the principles are no longer universally applied. Credit unions, if not co-operative banking, may not offer the financial assurances that commentators have called for. Moreover, the guiding principles may no longer be embedded within the fabric of the movement. Practical implications: Findings are important for practitioners/supervisory body as they highlight possible impacts on co-operative’ future and especially on their governance model and level of autonomy and independence in case of state intervention. Originality/value: The research undertaken is original as it is the first time credit unions in Cyprus were examined for adherence to co-operative principles.
Keywords: Co-operative principles; Co-operatives; Credit unions; Financial crisis; Governance